Lecturer’s Feedback and Students’ Writing Performance: Social Constructivism Perspective - Safitri, Heriani Dhia Ayu; Hamamah, Hamamah (Asatiza: Jurnal Pendidikan, 2021)
EFL writing as the form of productive skill has been the main issue for university students in Indonesia. Therefore, to maintain EFL students to be a good writer, lecturer’s feedback is necessary. The aims of this study were to find out whether there is any relationship between lecturer’s feedback and students’ writing performance, and to find out in what ways the lecturer’s feedback given seen from social constructivism. The researcher employed mixed method which took the data from 60 third-semester students in two Essay Writing Classes, and it was collected by using questionnaire, students’ writing score, and interview guide. The findings showed that correlation coefficient was .273 which indicates that the correlation between lecturer’s feedback and students’ writing performance was positive. While, seen from the significant level, it showed the number .042 which means there was statistically significant relationship between those two variables. The qualitative finding asserted that the lecturers always gave feedback frequently in the two forms, both were oral and written feedback. Other than that, although only one of the lecturers who used elaborated feedback, they both provide the assistance and objectivity during the assessment process. Based on the results of this study the lecturers must give feedback continuously towards students’ work and it should be given together with an explanation. Moreover, the future researcher can find the similar topic from another learning theory such as behaviorism or cognitivism.